The order of technology: Complexity and control in a connected world - Kallinikos, Jannis (Information and organization, 2005)
This paper examines some of the implications associated with the growing complexity of the contemporary world, consequent upon the expanding economic and organizational involvement of ICT-based systems and artefacts. Drawing on Luhmann, traditional forms of technological control are analyzed in terms of functional simplification and closure. Functional simplification involves the demarcation of an operational domain within which the complexity of the world is reconstructed as a simplified set of causal or instrumental relations. Functional closure implies the construction of a protective cocoon that is placed around the selected causal sequences to ensure their recurrent unfolding. While possible to analyze in similar terms, current developments, as manifested in the diffusion of large-scale information systems and mostly the internet spin a web of technological relations that challenge the strategies of functional simplification and closure and the organizational practices that have traditionally accommodated them.